Field ecology: Atlantic Forest Biome, coastal and marine environments (Environmental Smoke, 2024)
In this compilation, you will find the activities, ecological studies and experiences during the Field Ecology course, offered annually by the Graduate Program in Ecology and Environmental Monitoring (PPGEMA, UFPB, Brazil).The course took place from August 14 to 25, 2023 and PPGEMA students had the opportunity to gain a practical understanding of the development of research projects related to the different organisms belonging to the fauna and flora of the Atlantic Forest, Coral Reef and Mangrove Biome in the state of Paraíba.The activities were conceived and carried out with the guidance of PPGEMA professors and post-doctoral students, as well as the contributions of guest professors.We hope that this book will inspire all those who are interested in understanding how ecosystems work and the importance of maintaining our natural resources. May this work also stimulate the reader's curiosity and help them understand the importance of ecology as a science. And that it raises awareness of how fundamental it is to understand our resources, so that they can be preserved for future generations.